Colorimetric Sensors: Large‐Area Virus Coated Ultrathin Colorimetric Sensors with a Highly Lossy Resonant Promoter for Enhanced Chromaticity (Adv. Sci. 18/2020). Issue 18 (23rd September 2020) - Yoo, Young Jin; Kim, Won‐Geun; Ko, Joo Hwan; Kim, Yeong Jae; Lee, Yujin; Stanciu, Stefan G.; Lee, Jong‐Min; Kim, Seungchul; Oh, Jin‐Woo; Song, Young Min
Abstract : In article number 2000978, Jin‐Woo Oh, Young Min Song, and co‐workers propose a dynamically responsive virus (M‐13 phage)‐based changeable coloring strategy with a highly lossy resonant promoter (HLRP). The spatially designed colorimetric indicator, which responds rapidly to external stimuli, provides an intuitive perception of environmental changes with hidden/revealed patterns.